VEGETALES FOSILES DE LA FORMACION SPRINGHILL, CRETACICO, EN EL SUBSUELO DE LA CUENCA MAGALLANICA, CHILE (Ameghiniana, 2013)
This paper deals with the description of plant compressions and impressions found in subsurface cores, Springhill Formation, Magallanes Basin, Chile. The age of the formation is considered by dífferent authors as being Lowerrnost Cretaceous. The following taxa have been described: Ticoa magallanica n. sp., Otozamites sanctae-crucis Feruglio, emend., Zamites sp. (aff Z. gigas (L. et H.) Morrís ), Ptilophyllttm antarcticum Halle, Cucadolepis spp. a Bennettitalean inflorescence, Brachyphyllum feistmantelii (Halle) Sahni, emend. and Araucarites sp.